2009
DOI: 10.2320/matertrans.l-m2009816
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Deformation and Collision Behavior of Pure Aluminum Plates in Magnetic Pulse Welding

Abstract: In-situ observation of magnetic pulse welding process using a one-turn coil was performed by using a high-speed video camera. Highspeed deformation and collision behavior of the metal plates were investigated. The flyer plate traveled toward the parent plate with a high speed by the generated electromagnetic force. A collision velocity of the flyer plate to the parent plate was 250 m/s at the representative welding condition (initial gap distance between two plates: 1.0 mm, discharge energy: 2.5 kJ). It was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…In terms of application and properties, CS is perhaps best to be compared to thermal spraying processes, as in [24,25]. In view of relevant physical phenomena, however, CS is most closely related to explosive powder shock compaction, magnetic pulse welding (MPW) [26] and explosive welding. Likewise, some of the conventional thermal spraying processes, such as arc or plasma spraying where there is extensive melting and resolidification, may be best compared to fusion welding from the viewpoint of solidification science.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of application and properties, CS is perhaps best to be compared to thermal spraying processes, as in [24,25]. In view of relevant physical phenomena, however, CS is most closely related to explosive powder shock compaction, magnetic pulse welding (MPW) [26] and explosive welding. Likewise, some of the conventional thermal spraying processes, such as arc or plasma spraying where there is extensive melting and resolidification, may be best compared to fusion welding from the viewpoint of solidification science.…”
Section: Introductionmentioning
confidence: 99%
“…The welding interface exhibited characteristic wavy morphology, as well as similar and dissimilar metal joints. 1,13,14) A thin intermediate layer was also produced along the wavy interface. In the intermediate layer, several shadings of medium contrast between the aluminum and the metallic glass were observed.…”
Section: Welding Interface Of Lap Jointsmentioning
confidence: 99%
“…The collision speed estimated by Watanabe et al was 250 m/s, which is twice higher than the average collision speed (130 m/s) investigated in the same method of present study. 25) This difference is suggested to be due to electromagnetic force generated by the interaction of discharge current, magnetic ux and eddy current, which continues to accelerate the yer sheet until discharge current disappears. The pure Al sheet and the Al alloy used in the present study have different electrical conductivity and mechanical properties.…”
Section: Collision Speed and Weld Widthmentioning
confidence: 99%
“…Previously, Okagawa and Watanabe et al have reported on the collision speed of pure aluminum sheet and pure copper sheet. 19,25,26) However, there are still no studies on the lap joint of 2017-T3 or 2024-T3 sheets. Figure 7 shows the relationship of discharge energy, travelling velocity and collision time for both 2017-T3/ 2017-T3 and 2024-T3/2024-T3 lap joints when the gap is set to 1 mm.…”
Section: Collision Speed and Weld Widthmentioning
confidence: 99%
See 1 more Smart Citation